Manajemen Risiko & Bisnis Syariah - Sophia Kharisah (Islamic Education Journal, 2022)
Risk management in running a business is very important to do to protect the organization from risks that hinder the achievement of goals and various things that have the potential to cause losses to the company. This paper attempts to explain the basic concepts of risk management, the Islamic view of risk management, the relevance of risk and returns, and the urgency of risk management for sharia business. The results of this review can be concluded that there are two important rules that must be considered in conducting business and in every business transaction, namely the rules of al-kharaj bidh dhaman and al ghunmu bil ghurmi. With these two rules, Islam eliminates injustice and protects the rights of every party involved in the transaction business.